Pedagogical Communication and its Role and Significance in Developing the Professional Thinking of Students - Tokhirova Farida Olimjonovna (Genius Publishing Group, 2023)
This article discusses the need for people to work together, relationships, interactions, information and data exchange, and important educational issues in their pedagogical interactions with students.
Keywords: joint activity; need; exchange; connections